Carbon Nanotubes Decorated with CoP Nanocrystals: A Highly Active Non‐Noble‐Metal Nanohybrid Electrocatalyst for Hydrogen Evolution1. Issue 26 (20th May 2014) - Liu, Qian; Tian, Jingqi; Cui, Wei; Jiang, Ping; Cheng, Ningyan; Asiri, Abdullah M.; Sun, Xuping
Abstract The development of effective and inexpensive hydrogen evolution reaction (HER) electrocatalysts for future renewable energy systems is highly desired. The strongly acidic conditions in proton exchange membranes create a need for acid‐stable HER catalysts. A nanohybrid that consists of carbon nanotubes decorated with CoP nanocrystals (CoP/CNT) was prepared by the low‐temperature phosphidation of a Co3O4/CNT precursor. As a novel non‐noble‐metal HER catalyst operating in acidic electrolytes, the nanohybrid exhibits an onset overpotential of as low as 40 mV, a Tafel slope of 54 mV dec−1, an exchange current density of 0.13 mA cm−2, and a Faradaic efficiency of nearly 100 %. This catalyst maintains its catalytic activity for at least 18 hours and only requires overpotentials of 70 and 122 mV to attain current densities of 2 and 10 mA cm−2, respectively.